First report of Paramyrothecium roridum causing leaf spot and stem rot diseases on Coffea arabica in Peru - Huamán-Pilco, Angel Fernando; Huamán-Pilco, Jorge; Torres-de la Cruz, Magdiel; Oliva-Cruz, Segundo Manuel; Díaz-Valderrama, Jorge Ronny (Plant disease, 2023)
Peru is the ninth exporter of coffee ( ) in the world, and Amazonas is among its most important producing departments (INIA 2019). In July 2021, in the nursery of the "Instituto de Investigación para el Desarrollo Sustentable de Ceja de Selva", in Huambo district (6° 26' 11.19'' S; 77° 31' 24.18'' W), four-month-old coffee seedlings cv. Catimor with 0.5-2.0 cm brown concentric leaf spots and rotten stems, bearing white mycelial tufts and black sporodochia, were observed at 30% incidence. Infected seedlings were collected. Foliar sections of 2-3 mm with infected tissue were surfaced disinfected in 2% NaClO and transferred onto Petri plates containing potato dextrose agar medium (PDA). The plates were incubated at 25° C for 7 days. We obtained three isolates (INDES-AFHP61, INDES-AFHP62 and INDES-AFHP66) with similar morphology from different seedlings. Colonies (16-17 mm diam.) formed concentric rings with white aerial mycelium, giving rise to viscous and olivaceous dark green sporodochial conidiomata. Conidia (4.82-5.77 × 1.34-1.65 µm; n = 30) were cylindric, hyaline, smooth, and aseptate. These morphological features correspond to spp. (Lombard et al. 2016). The DNA of isolates was extracted using the Wizard® Purification Kit (Promega Corp., Madison, Wisconsin), and the internal transcribed spacer 1 and 2 intervening the 5.8S subunit rDNA region (Accession numbers: OM892830 to OM892832), and part of the second-largest subunit of the RNA polymerase II, the calmodulin and the β-tubulin genes (OM919453 to OM919461) were sequenced following Lombard et al. (2016). All sequences had a percent identity greater than or equal to 99% to corresponding sequences of the type specimen (CBS 357.89). Additionally, a multilocus Maximum Likelihood phylogenetic analysis incorporating sequence data from previous relevant studies (Lombard et al. 2016; Pinruan et al. 2022) grouped our three isolates together with the type and other specimens of in a strongly supported clade, confirming the species identification. To evaluate pathogenicity, four-month-old coffee seedlings cv. Catimor were sprayed with 10 mL of conidial suspensions at 1 x 10 /mL. A set of control seedlings were inoculated with sterile water. Seedlings were maintained in a humidity chamber at 25 °C. After 15 days brown concentric foliar spots, stem rotting, mycelial tufts and sporodochia (same symptoms and signs observed originally at the nursery) arose in the non-control seedlings. The pathogen was re-isolated on PDA, confirming was the causal agent of leaf spot and stem rot diseases of coffee. has wide geographic distribution and host range (Lombard et al. 2016). This pathogen was reported to infect in Mexico and sp. in Colombia (Pelayo-Sánchez et al. 2017; Lombard et al. 2016; Huaman et al. 2021). It was also reported in Africa infecting soybeans (Haudenshield et al. 2018), in Brazil infecting (Borges et al. 2018), in Egypt infecting strawberries (Soliman 2020), and in Malaysia infecting (Hassan et al. 2021). To the best of our knowledge, this is the first time is reported on coffee in Peru.